Mobile applications for real time market information and decision support in horticultural crops - Burman, Rajarshi Roy; Mahra, Girijesh Singh; Mallick, Sonali (Indian Horticulture, 2025)
The transformative impact of mobile applications on the horticultural sector, highlighting their role in providing real-time market information and decision support has been well established. With the increasing adoption of smartphones among farmers, mobile based applications have become essential tools for accessing vital data, including weather forecasts, market prices, and crop management practices. By bridging the information gap, mobile apps empower farmers to make informed decisions, enhance productivity, and optimize their operations. User-friendly design, offline functionality, and robust data security are essential features that enhance the accessibility and trustworthiness of these applications, especially for farmers in remote areas. Ultimately, the integration of mobile technology into horticulture represents a significant advancement towards sustainable agricultural practices and improved livelihoods for farmers worldwide.